Preparation And Optimization Of Process Variables Of Nanoparticles Contaning Anti Cancer Drug - VIVEK KUMAR GUPTA; P.K.KARAR (International Journal of Pharma and Bio Sciences, 2012)
The objective of the present study is to formulate nanoparticles that contain 5-Flurouracil, an anticancer drug and optimization for chemical properties, drug concentration, polymer concentration, cross-linking agent and stirring speed. Nanoparticles of 5-Flurouracil were formulated using chitosan polymer and pregelated Sodium alginate by Ionotropic pregelation method. Calcium chloride was also included in the formulation for pregelation of sodium alginate. Prepared 1% acetic acid solution of chitosan and pregelated calcium alginate suspension further cross linked with Gluteraldehyde. Different formulations of nanoparticles were prepared using different concentrations of chitosan, stirring speed, time of rotation and polymer to drug ratio in the nanoparticles. The average particle size ranged between 246 nm to 620 nm. Drug entrapment ranged between 71.97%-89.90%. The result indicated that the drug loaded nanoparticles of 5-Flurouracil showed optimum particle size and maximum drug entrapment with drug polymer ratio 05:75, cross-linking agents 02 ml, stirring rate 800 rpm and stirring time 90 min.